THE POTENTIAL AND DISTRIBUTION OF BIOPESTICIDES PLANTS AROUND RIAU UNIVERSITY CAMPUS - Agus Sutikno; Defri Yoza; Vini Volcherina Darlis (Jurnal Ilmu Ilmu Kehutanan, 2020)
This study aims to determine the potential of plants as biopesticides found around Riau University campus. The method used consists of vegetation analysis and renaissance methods. The vegetation analysis method was used in the arboretum area of the Riau University while the renaissance survey was carried out on agricultural gardens, shrubs and road shade plants. From the survey results, there were 25 types of botanical pesticide with the highest growth rate at at the seedling and understorey plants.